Analisa Dampak Regulasi Pemerintah dan Kenaikan Bea Cukai untuk Minuman Mengandung Etil Alkohol (MMEA) terhadap Pemerintah, Konsumen dan Produsen Alkohol di Jakarta - Devona Theodora Sukamto (Universitas Tarumanagara, 2022)
This research aims to analyze the impact of alcohol tax and the new government regulation regarding alcoholic drinks. Alcoholic drinks, while it may not be a main income for the country is also one of the most consumed beverages. There are 3 types of categories in regards to alcoholic drinks all according to their alcohol percentage. Each category possesses different tax rates. It is known that the alcohol tax in Indonesia is quite high. This research uses a qualitative method to get in-depth knowledge from the producer/supplier/bar or restaurant owner of alcoholic drinks and also a consumer. Data from consumers are derived using a survey meanwhile the other party’s data is conducted by an interview. There are several in-depth analyses regarding the regulations and also the data that has been taken by the researcher. This research also aims to make awareness regarding the governing law and the impact that it has on the people in this country. Penelitian ini bertujuan untuk menganalisis dampak pajak alkohol dan peraturan pemerintah yang baru tentang minuman beralkohol. Minuman beralkohol, meski mungkin bukan pendapatan utama negara, juga merupakan salah satu minuman yang paling banyak dikonsumsi. Ada tiga jenis kategori minuman beralkohol yang semuanya menurut persentase alkoholnya. Setiap kategori memiliki tarif pajak yang berbeda. Diketahui pajak alkohol di Indonesia cukup tinggi. Penelitian ini menggunakan metode kualitatif untuk mendapatkan pengetahuan yang mendalam dari produsen/pemasok/bar atau pemilik restoran minuman beralkohol dan juga konsumennya. Data dari konsumen diperoleh melalui survei sedangkan data pihak lain dilakukan dengan wawancara. Ada beberapa analisis mendalam mengenai regulasi dan juga data yang telah diambil peneliti. Penelitian ini juga bertujuan untuk menyadarkan tentang undang-undang pemerintah dan dampaknya terhadap masyarakat di negeri ini.